Causas de óbito em pacientes com Lúpus Eritematoso Sistêmico internados na Fundação Santa Casa de Misericórdia do Pará - REIS, Luciana de Carvalho (2022)
This retrospective study analyzed the causes of death in 33 pacients with systemic lupus erythematosus who died during inernment at Fundação Santa Casa de Misericórdia do Pará, from january 1990 to december 2005. Objectives: Knowing principal causes of death of pacients with systemic lupus erythematosus and another points: mean age at diagnostic and death, the skin colour and the sex most prevalent, the clinical manifestation most prevalent at diagnostic and during the SLE development. Methods: It’s was made a revise at the promptuaries in the Fundação Santa Casa de Misericórdia do Pará file and filled an investigation protocolo made by the authors, based at clinical and diagnostic eminent points. The software Biostat 4 was used to computer and analyze the data. It was made comparison between the causes of death proportions and the variable categories proportions through the chi-square (X²); the statistic significative results were marked with an asterisk (P< 0.05). Results: Female gender was the most prevalent, 93.9%, while male gender was 6.1%; the non-white skin people were 75.8% and the white skin were 15.2%; the main age at death was 25.2 years.The main causes of death were sepsis (36.4%), nephritis (33.3%) and pulmonary causes (15.2%); there were no deaths due vascular causes, while the cardiac ones were just 6.1%; Conclusion: This study showed sepsis as the most common cause of death. The small cases of death due cardiovascular causes differs to literature. All patients who died because of sepsis and nephrologic causes used corticosteroid during the inerment.